Case Report: Adjuvant image-guided radiation therapy reduces surgical invasiveness in malignant peripheral nerve sheath tumors - Harikar, Mandara M.; Ferini, Gianluca; Palmisciano, Paolo; Shakir, Muhammad; Amico, Paolo; Ferraresi, Stefano; Umana, Giuseppe E. (Frontiers in Oncology, 2023)
Introduction Malignant peripheral nerve sheath tumors (MPNSTs) are a group of rare soft tissue sarcomas of mesenchymal origin. These tumors generally require extensive local excision owing to their aggressive potential. Though the role of radiotherapy is controversial, in this report, we present the case of an MPNST in the forearm that was treated with microsurgery followed by image-guided radiation therapy to achieve complete tumor disappearance at the 18-month follow-up. Case report A 69-year-old woman with underlying paranoid schizophrenia was referred to our department with pain, severe swelling, and ecchymosis of her right forearm. Physical examination showed hypoesthesia in the segments innervated by the median nerve and reduced motor strength of her right hand. A gadolinium-enhanced MRI showed a large malignant peripheral nerve sheath tumor (13 x 8 x 7 cm) of the median nerve in the forearm. She underwent microsurgical en-bloc tumor resection with sparing of the median nerve. Thirty-five days postoperatively, she underwent image-guided radiotherapy (IGRT) using volumetric modulated arc therapy (VMAT). Serial MRI scans of the forearm with Gadolinium and whole-body CT scan with contrast enhancement at 30 days, 6 months, 1 year, and 18 months postoperatively documented no tumor recurrence, remnants, or metastases. Conclusions In this report, we demonstrate the successful use of advanced radiotherapy techniques such as IGRT while avoiding demolitive surgery for MPNST. Though a longer follow-up is necessary, at the 18-month follow-up, the patient demonstrated good outcomes from surgical resection followed by adjuvant RT for MPNST in the forearm.